USO DE ÓLEO ESSENCIAL DA LIPPIA ORIGANOIDES NO DESEMPENHO PRODUTIVO DO PACU (PIARACTUS MESOPOTAMICUS) - XAVIER, Vitória Maria Gregório,; MENDEZ, Victor Hugo Benassi,; ACUNHA, Rubia Mara Gomes,; 2ALMEIDA, Rômullo Guilherme dos Santos,; AMARAL, Cristiane Meldau de Campo, (ANAIS DO ENIC, 2024)
-